Pradzieje okolic Szadku w zarysie - Rapiejko, Adam (Biuletyn Szadkowski, 2008)
This article spans the period from prehistoric times to the early Middle Ages. It presents the history of pre- and post- war history of research carried out on the territory of the present-day commune of Szadek, and a short review of the history of settlement in this region with a list of archaeological sites in the area. The earliest archaeological works were conducted there in the second half of the 19th century, when a cinerary-urn cemetery was found in the “Old Town” and amateur-archaeologists made discoveries in the neighbourhood of Piaski. A particularly interesting excavation site is in Przyrownica (Wola Łobudzka) with a Przeworsk culture cemetery, which was functioning for about 200 years.